Profil Perawatan Sendiri (Self-care) dan Swamedikasi (Self-medication) pada Madrasah Aliyah Berasrama di Aceh Besar selama Masa Pandemi COVID-19 - Abdul Hakim; Novia Maulina; Hajar Sugihantoro; Humaira Ramzi (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
The COVID-19 pandemic has brought many changes to society, especially in carrying out daily activities. One of the changes is an increase in self-care and self-medication as an effort to survive during the COVID-19 pandemic. This research was conducted at Madrasah Aliyah (MA) Ruhul Islam Anak Nation Aceh Besar. The school is a boarding school that conducts offline learning activities during the COVID-19 pandemic. The purpose of this study was to find out the description of self-care and self-medication during the COVID-19 pandemic at MA Ruhul Islam Anak Bangsa Aceh Besar. The research method uses descriptive research methods. Data was collected by filling out the questionnaire directly using a sample of 90 respondents. The results showed that the self-care profile showed that respondents who always made efforts to prevent COVID-19 were 21.9% and respondents who always maintained their well-being were 34.4%. In the self-medication profile, data showed that when self-medication, most of the respondents used synthetic drugs (69.5%), most of the respondents received information about self-medication from their parents (57.3%), the purpose of doing self-medication was mostly to increase endurance (45.1%), when doing self-medication, there are respondents who experience side effects, and the most are dizziness (29.1%) and 56.5% of respondents will immediately stop treatment if there are side effects, The most obstacles experienced by respondents in carrying out self-medication was that respondents did not know what medicine to use (40.2%). Based on these results, it can be concluded that it is necessary to increase the prevention of COVID-19 and provide education in conducting self-medication during the COVID-19 pandemic at the Supreme Court of Ruhul Islam Anak Bangsa Aceh Besar.